Designing IPAER Learning Model in IPAS Learning: an Effort to Improve Critical Thinking Skills in Elementary School - Nasyariah Siregar; Syahrial Syahrial; Sofyan; Bunga Ayu Wulandari (Postgraduate, University of Mataram, 2025)
Critical thinking skills are important for students today. Teachers play an important role in developing students' abilities in the classroom. However, it is often found that students' critical thinking skills are low, due to the use of inappropriate learning models. Therefore, this study aims to design an IPAER learning model as an alternative to dealing with these problems. This research is a research and development, referring to the ADIIE model. Data collection uses a needs analysis instrument, IPAER learning model feasibility instrument, IPAER learning model practicality instrument, and IPAER learning model effectiveness instrument in improving critical thinking skills. The results showed that the IPAER model had been declared valid by experts and had been adjusted to empirical theory.